CBCT imaging study on adult pterygoid hamulus and their adjacent tissues - WANG Zhenting, LI Bei, JI Yi, ZHANG Juan, YANG Chen, SHAN Hua, LIU Rui (Kouqiang yixue)
Objective To analyze the morphology of the pterygoid hamulus and its relationship with adjacent tissues on CBCT images, establish reference data of the anatomical structure of the pterygoid hamulus in the adult population, in order to provide a basis for clinical assisted diagnosis and treatment of pterygoid hamulus syndrome and obstructive sleep apnea hypopnea syndrome. Methods A total of 151 patients with CBCT images who met the inclusion criteria were collected from August 2020 to December 2023 in the Department of Stomatology at the Second Traditional Chinese Medicine Hospital of Jiangsu Province. The CBCT images were reconstructed using the maximum intensity projection(MIP) and volume rendering(VR) modes of cone-beam CT. The morphology, length, width, vertical height, abduction angle, mucosal thickness, distance from the pterygoid hamulus to the midline of the palate, and distance from the pterygoid hamulus to the greater palatine foramen were observed and statistically analyzed in 302 bilateral cases. The differences in the morphology of the pterygoid hamulus and its adjacent tissues were analyzed in different places, genders and age groups. Results The apex of the pterygoid hamulus faced inward on 6 sides and outward on 296 sides. The apex of the pterygoid hamulus was sharp on 46 sides and blunt on 256 sides. The pterygoid hamulus showed no statistically significant differences in various parameters between the left and right sides, except for the width. In males, the length, width, height, distance from the pterygoid hamulus to the mid-palatal suture, and mucosal thickness on the surface of the hamulus were all greater than those in females, demonstrating statistically significant differences. Females also exhibited a larger outward angle of the pterygoid hamulus than males, which was statistically significant. Moreover, with the increase of age, the length and height of the pterygoid hamulus initially increased and then decreased, exhibiting statistically significant differences. Conclusion CBCT has the advantages of low radiation dosage, convenient operation, clear imaging, stable measurement data, and clear images in the examination of pterygoid hamulus. It helps in the diagnosis and treatment of pterygoid hamulus-related diseases in a clinical setting.